Incidentalomy hypofýzy - Kršek, Michal (Vnitrni lekarstvi, 2022)
Pituitary incidentaloma are being accidentally found during imaging procedures in approximately 10% of normal population. Facing pituitary incidentalomas endocrinologists have to decide about further management based on the assessment of hormonal activity, aetiology, size, and possible compressive symptoms. Treatment of choice for prolactinomas is medical therapy. Surgical treatment is a treatment of choice for other hormonally active tumours and in case of complications as defects of visual field, pituitary apoplexy with compressive symptoms, ophthalmoplegia respectively. Tumour not indicated for surgical treatment are followed-up by imaging techniques and in indicated cases also by endocrinological or visual field evaluation.
Keywords: prolaktinom; therapy; Humans; Prolactinoma; monitoring; diagnosis; incidentaloma; tumor; tumours; Pituitary Apoplexy; Endocrinology; follow‑up; Pituitary Neoplasms; nádory hypofýzy; pituitary; endokrinologie; lidé; type 2 diabetes; adenom; Adenoma; apoplexie hypofýzy